2016
DOI: 10.1002/ldr.2477
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cattle Manure Effects on Soil Quality: Porosity, Earthworms, Aggregates and Soil Organic Carbon Fractions

Abstract: In the European Union, the maintenance of soil quality is a key point in agricultural policy. The effect of additions of dairy cattle (Bos taurus) manure (DCM) during a period of 11 years were evaluated in a soil under irrigated maize (Zea mays L.) monoculture. DCM was applied at sowing, at wet-weight rates of 30 or 60 Mg ha À1 yr À1 (30DCM or 60DCM). These were compared with a mineral-N treatment (300 kg N ha À1 , MNF), applied at six to eight emerged leaves and with a control (no N, no manure). Treatments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 66 publications
2
28
0
1
Order By: Relevance
“…Moreover, long‐term minimum soil disturbances under NT coupled with SR greatly favour soil aggregation (Kahlon et al ., ; Lenka & Lal, ; Busaria, Kukal, Kaur, Bhatt, & Dulazi, ; Nath & Lal, ). The lower MWD under CT could be mainly ascribed to mechanical disruption of macroaggregates from frequent tillage operations and reduced aggregate stability (Mikha et al ., ; Nath & Lal, ; Yagüe et al ., ; Zhang‐liu et al ., ). Du, Ren, Hu, Zhang, & Blanco‐Canqui () reported higher MWD under NT with residue retained than mouldboard plough with residue retained after 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, long‐term minimum soil disturbances under NT coupled with SR greatly favour soil aggregation (Kahlon et al ., ; Lenka & Lal, ; Busaria, Kukal, Kaur, Bhatt, & Dulazi, ; Nath & Lal, ). The lower MWD under CT could be mainly ascribed to mechanical disruption of macroaggregates from frequent tillage operations and reduced aggregate stability (Mikha et al ., ; Nath & Lal, ; Yagüe et al ., ; Zhang‐liu et al ., ). Du, Ren, Hu, Zhang, & Blanco‐Canqui () reported higher MWD under NT with residue retained than mouldboard plough with residue retained after 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Various workers have reported that soil aggregates are stabilised by diverse mechanisms and perform differently against external factors, namely, rain, wind, irrigation and other farm management practices (Blanco‐Canqui & Lal, ; Bronick & Lal, ). These management practices in turn influence the relative distribution of aggregate mass, their stability (Cerdà, ; Saygin, Erpul, & Basaran, ; Yagüe, Domingo‐Olivé, Bosch‐Serra, Poch, & Boixadera, ; Mamedov, Huang, Aliev, & Levy, ) and the distribution of C and nitrogen (N) in these aggregates (Bandyopadhyay & Lal, ; Sundermeier, Islam, Raut, Reeder, & Dick, ). Of late, worldwide conservation agriculture (CA)/no‐till (NT) farming has gained impetus, and land under the CA regime has increased in area up to 124 m ha −1 by 2012 (Friedrich, Derpsch, & Kassam, ; Palm, Blanco‐Canqui, DeClerck, & Gatere, ), which was considered a sustainable and feasible approach to improve soil aggregation and also sustain or increase SOC (Powlson, Whitmore, & Goulding, ; Dalal, Allen, Wang, Reeves, & Gibson, ; Kahlon, Lal, & Varughese, : Palm et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased porosity between and inside the aggregates offer more space for maintaining and exchanging water and air, which prevent the leaching of cations and support more abundant and diverse microbes (Nardi, ) for nutrient transfer by metabolic activities (Chenu, Le Bissonnais, & Arrouays, ). It has been reported that the land use and soil management could alternate the soil characters, including the formation of aggregates (Barthes & Roose, ; Kotzé, Sandhage‐Hofmann, Amelung, Oomen, & du Preez, ; Yagüe, Domingo‐Olivé, Bosch‐Serra, Poch, & Boixadera, ; Zhu, Shangguan, & Deng, ) that in turn affect the above‐ground ecological processes. In some grasslands, long‐term grazing exclusion and grazing managements could enhance the soil aggregate formation (Wen, He, & Zhang, ), improve soil organic matter stability and stock (Silveira, Xu, Adewopo, Franzluebbers, & Buonadio, ), and increase aggregate stability (Li, Wang, Ma, & Li, ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil aggregate stability is one of the most important properties in soils and affects water erosion, soil aeration, nutrient recycling, and biological activity, as well as plant growth (Cerdà, ; Le Guillou, Angers, Maron, Leterme, & Menasseri‐Aubry, ; Moncada, Gabriels, Cornelis, & Lobo, ). Physical forces, chemical bonds, and biological agents may drive the aggregation processes of soil particles (Lehmann & Rillig, ; Yagüe, Domingo‐Olivé, Bosch‐Serra, Poch, & Boixadera, ). Microaggregate stability is an important soil property that is usually used to determine soil erosion resistance (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%